Academic Senate Minutes 2006-03-09 - Academic Senate:::::::::
Chair's Report. Agenda amended and approved. Minutes of 2/23/06 approved. Information Item: SAC Advising Best Practices. Special Guest: Dr. Kay Dorner from the Technology High School (and many students). Provost Report. Statewide Senator Report. Associated Students Report. Chair-Elect report. All Standing Committees reported. Consultation Policies postponed to next meeting. Standing Rule on Senate-Talk approved. Resolution on Green Music Center first reading. Priority Registraion Policy first reading. FSAC Resolution on Faculty Workload first reading